The antecedents and innovation outcomes of firms’ absorptive capacity in global buyer–supplier relationships - Wang, L.; Li, Jun (2016)
This article seeks to address two fundamental questions: (1) Does social capital (SC) embedded in global buyer–supplier (GBS) relationships enhance local firms’ potential absorptive capacity (PAC) and realized absorptive capacity (RAC)? And (2) What are the effects of local firms’ PAC and RAC on their innovation outcomes? Based on survey data collected from 297 Chinese firms engaged in GBS cooperation in China’s Yangtze River Delta region, we test our research hypotheses with the structural equation modelling approach. The empirical findings indicate that both structural and relational SC are important antecedents of PAC and RAC in global buyer–supplier relationships. More specifically, RAC not only improves local suppliers’ new product performance, but also fully mediates the relationship between PAC and new product performance. Our results have two major implications for practicing managers. First, local suppliers in emerging economies need to pay more attention to SC embedded in GBS relationships for it is an important means for them to overcome resource constraints and therefore to improve their new product performance. Second, it is important for managers in local firms to continuously improve their PAC to better assess and assimilate external knowledge, and extend their RAC to upgrade their interpretation and comprehension of commercialization possibilities, which allows for generating synergy of knowledge recombination with existing core competencies.